(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The article considers certain provisions of the well-known American folklorists M. Parry and A. Lord from critical and constructive points of view. The concept of Parry-Lord mainly focused on the key issue – the epic formulae, its nature, its structure, functions, and especially its dominant role in creation of a new text in the process of improvisation. From the analysis of the Kazakh study of epic poetry, it can be observed that some researchers had paid their attention to the nature of the oral-style techniques before the theory of Parry-Lord. In connection with the history of formation of the Kazakh epics such ideas were expressed by M.O. Auezov and O.A. Nurmagambetova in terms of its true connection with the ancient genres of folklore and with ceremonial and ritual traditions. The fundamental scientific discoveries of B.Sh. Abylkasimov, Ш. Ибраев, J.J.Bekturov, S. Negimov and other researchers play the most important role in our science. At the same time, individual approaches by these researchers in this article have been exposed from the point of constructive criticism, as well as some aspects of the concept of Parry-Lord.